Seasonal muscular power changes: Considerations of concurrent resistance and field-based training in professional Rugby League - Redman, K. J.; Wade, L.; Whitley, R.; Connick, M. J.; Kelly, V. G.; Beckman, E. M. (The Journal of Strength and Conditioning Research, 2024)
A rugby league player's ability to develop or maintain lower-body power will be significantly influenced by the resistance and field-based training loads completed. This study aimed to examine the power changes across a rugby league season and to investigate the relationship of concurrent training and training experience on power changes. Eighteen rugby league players participated in this study. Lower-body power was evaluated using a countermovement jump throughout the season. Four measures of external training loads were collected. A Friedman's test was used to assess differences in power throughout different phases of the season. A series of Spearman's rank-order correlations were conducted to assess the relationship between percentage changes in power during the training block, external training loads, and training experience. Countermovement jump peak velocity significantly decreased from the start (p = 0.006) and end of pre-season (p = 0.022) to the late competition. Correlation analysis revealed a large significant association between early competition field-based external loads (relative (rs = -0.571) and total distance (rs = -0.628)) and change in peak power. Very large significant negative relationships were also observed between mid-competition volume load with change in peak force (rs = -0.825) and peak power (rs = -0.736). Training experience was not significantly associated with changes in muscular power variables throughout this study. Coaches should seek to monitor changes in peak power when competition begins and to assist with decision-making for potential adjustments to running volume and intensity during field-based sessions.